Effects of Sahaja Yoga Meditation on Frequency and Intensity of Earthquake in Palghar District - Takpere, Sanjay; Jadhav, Jagdish; Takpere, Purva; Patil, Sachin; Sawant, Nilima (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Sahaja Yoga (SY) is a unique method of experiential meditation based on Self Realisation (Kundalini Awakening) which can occur in any human being. Through Sahaja Yoga Meditation, an inner transformation takes place by which one becomes balanced, united and integrated. Sahaja Yoga has an impact on a person and society. The meditation is based on “Energy centres” i.e., Chakras and Channels i.e., Nadis. The human body is made up of the five elements (Pancha Maha Bhootas) i.e., earth (Prithvi), water (Jala), fire (Tejas), wind (Vayu) and space (Akasha). Our body works in synchronisation with these 5 elements. Sahaja Yoga Meditation (SYM) is found to bring about the balance in these elements. Similarly, SYM is found to have effects on nature which is also made up of these five elements. The statistical analysis of earthquake data for the Palghar district suggests that the mean and variation (standard deviation) of earthquake magnitude is lowered during the period of SY Realization programs. I-MR Control Charts indicate that earthquakes become more stable after SY Realization programs. Pareto Charts indicate that the magnitude of earthquakes and their frequencies decline during and after SY Realization programs.